Fishermen’s Competency in the Use of Modern Electronic Equipment in Deep-Sea Fisheries of Tamil Nadu, India - Sendurpandian, Viswanathan (Faculty of Fisheries and Marine Science, Brawijaya University, Malang, Indonesia, 2026)
The increasing adoption of electronic navigation, communication, and monitoring technologies has transformed fishing vessel operations; however, the benefits of these systems depend strongly on fishermen’s competency in using them effectively. This study assesses the availability, usage, and competency levels of fishermen operating modern electronic equipment on deep-sea fishing vessels in Tamil Nadu, India. The key variables examined include fishermen’s competency scores in using ten categories of electronic equipment (GPS, AIS, RADAR, electronic charts, echo sounder, magnetic compass, VHF radio, NAVTEX/NavIC/GEMINI, barometer, and anemometer), along with demographic factors (age, education), operational characteristics (vessel type, vessel length, distance travelled), and harbour location. A competency framework was developed using a four-point ordinal scale ranging from unfamiliarity to confident operation, yielding a maximum composite score of 40. Data were collected from 405 fishing vessel drivers across six major fishing harbours from Tamilnadu using a convenience sampling approach, representing approximately 20% of fishing vessel drivers at each harbour. Statistical analyses were performed using Jamovi, Excel, including descriptive statistics, Shapiro–Wilk tests for normality, Kruskal–Wallis H tests for group comparisons, and Spearman’s rank correlations to examine relationships between competency and explanatory variables. Instrument reliability was confirmed using Cronbach’s alpha (α > 0.8). Results reveal significant variations in competency across fishing harbours and vessel types (p < 0.001). Age and education were positively associated with competency, whereas vessel length and distance travelled were negatively correlated. Notably, awareness and usage of advanced systems such as NAVTEX, NavIC, GEMINI, barometers, and anemometers were low, whereas GPS, AIS, and electronic charts were more widely adopted. The study concludes that technology availability alone is insufficient; targeted training and capacity-building interventions are essential to improve competency, enhance safety, and promote sustainable fishing practices in Tamil Nadu.